Incidencia de malezas sobre la agronomía y rendimiento del cultivo de arroz (Oryza sativa L.), utilizando diferentes fuentes y niveles de nitrógeno. - Verdesoto Calero, Genesis Viviana (2019)
. SUMMARY The present research work was carried out in The present experimental work was carried out in the lands of the Hacienda Sofia, located at km. 13 of the Babahoyo-Montalvo road: Precinct "May 24"; with geographic coordinates of 79º18' of West Longitude and 1º47'of South Latitude, and with a height of 12 m.s.n.m. The annual average temperature is 24.5ºC, an average annual rainfall of 2,203 mm and 1,006 hours of heliophany, The area has a monsoon tropical climate (AM), the rainy season includes from December to May, and the dry season of June to December, with an altitudinal range from 6 to 400 meters above sea level. Seeds of rice, variety SFL-11, were used as seed material. The treatments were constituted by the different doses of fertilizers such as 90, 120, 150 kg / ha; plus a control treatment without application of the product. The experimental design Complete Random was used with seven treatments and 3 repetitions, the test of significance used was Tukey at 95% probability. All the necessary agricultural work was carried out in rice cultivation for its normal development as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the following data were taken: plant height, tillers, root length, leaf area, panicles per plant, panicle length, grains per panicle, weight of 1000 seeds, grain yield, economic analysis. For the results obtained it was determined that the incidence of weeds affected the agronomic development of the crop, which could be observed in all the variables evaluated except for the leaf area, the T3 treatment with the chemical source (Urea), at a dose of 150 kg of N was the main cause of decline in productivity of rice cultivation with 2149.87 kg / ha; Therefore, the importance of carrying out new research on the effect of fertilization on the incidence of weeds in agriculture is reflected. Keywords: fertilizers, rice crop yield.